Trekking Through Syntax: Navigating the Rules of Language - Hafizha, Aisyah; Nasyifa, Nazry; Sahmarito Rambe, Susi; May Azura, Anisa; Aldira Lubis, Nisa; Nur Amalia, Fadiah; Arkan Syafiq, Muhammad; Ismahani, Siti (Jurnal Pendidikan Tambusai, 2023)
This exploration delves into the realm of syntax within language, unraveling its profound influence on linguistic structure and communication. Termed as the navigational guide through the labyrinth of words, syntax emerges as the orchestrator dictating the arrangement, coherence, and interpretation of our expressions. Employing a fusion of library-based research and comprehensive literature review, diverse studies within this discourse unfold the evolution of syntax, its role in machine learning systems, and its integration into user-friendly interfaces. This holistic examination spotlights syntax as the fundamental framework shaping human expression and comprehension across diverse linguistic landscapes.